Association Between Succinate Receptor SUCNR1 Expression and Immune Infiltrates in Ovarian Cancer - Zhang, Jiawen; Zhang, Qinyi; Yang, Yongbin; Wang, Qingying (Frontiers in Molecular Biosciences, 2020)
Background: The activation of succinate receptor 1 (SUCNR1) by extracellular succinate has been found to regulate immune cell function. However, the clinical significance of SUCNR1 in ovarian cancer and its correlation with tumor-infiltrating lymphocytes remain unclear. Methods: The genetic alteration and expression pattern of SUCNR1 were analyzed by using cBioPortal and Gene Expression Omnibus (GEO) datasets. Kaplan-Meier Plotter was used to assess the prognostic value of SUCNR1 in patients with ovarian cancer. The correlation between SUCNR1 expression and immune infiltration, gene markers of immune cells, cytokines, chemokines or T cell exhaustion was explored by using TIMER and TISIDB platforms. We also performed Gene Set Enrichment Analysis (GSEA) to reveal biological function of SUCNR1 in ovarian cancer. Results: The expression of SUCNR1 was closely related to tumor infiltrating lymphocytes, multiple gene markers of immune cells and T cell exhaustion in ovarian cancer. The expression of SUCNR1 was also associated with the expression of cytokine- or chemokine-related genes. Moreover, GSEA revealed that various immune-related pathways might be regulated by SUCNR1. In addition, we found that SUCNR1 was amplified in ovarian cancer, and high expression of SUCNR1 predicted worse progression free survival (p = 0.0073, HR = 1.49, 95% CI = 1.11-2). Conclusions: These results highlight the role of SUCNR1 in regulating tumor immunity of ovarian cancer.